Effect of O-methyl-β-cyclodextrin-modified magnetic nanoparticles on the uptake and extracellular level of l-glutamate in brain nerve terminals - Horák, Daniel; Beneš, Milan; Procházková, Zuzana; Trchová, Miroslava; Borysov, Arsenii; Pastukhov, Artem; Paliienko, Konstantin; Borisova, Tatiana (Colloids and surfaces. B, Biointerfaces, 2017)
Changes in cholesterol concentration in the plasma membrane of presynaptic nerve terminals nonspecifically modulate glutamate transport and homeostasis in the central nervous system. Reduction of the cholesterol content in isolated rat brain nerve terminals (synaptosomes) using cholesterol-depleting agents decreases the glutamate uptake and increases the extracellular level of glutamate in nerve terminals. Extraction of cholesterol from the plasma membrane and its further removal from the synaptosomes by external magnetic field can be achieved by means of magnetic nanoparticles with immobilized cholesterol-depleting agent such as O-methyl-β-cyclodextrin (MCD). A simple approach is developed for preparation of maghemite (γ-Fe2O3) nanoparticles containing chemically bonded MCD. The method is based on preparation of a silanization agent containing MCD. It is synthesized by the reaction of triethoxy(3-isocyanatopropyl)silane with MCD. Base-catalyzed silanization of superparamagnetic γ-Fe2O3 provides a relatively stable colloid product containing 48μmol of MCDg(-1). MCD-modified γ-Fe2O3 nanoparticles decrease the initial rate of the uptake and accumulation of l-[(14)C]glutamate and increase the extracellular l-[(14)C]glutamate level in the preparation of nerve terminals. The effect of MCD-immobilized nanoparticles is the same as that of MCD solution; moreover, magnetic manipulation of the nanoparticles enables removal of bonded cholesterol.
Keywords: biologický transport; Carbon Radioisotopes; mozek; magnetické nanočástice; Brain; synaptozomy; membránové potenciály; radioizotopy uhlíku; Magnetite Nanoparticles; Membrane Potentials; zvířata; buněčná membrána; Presynaptic Terminals; Rats; beta-Cyclodextrins; Synaptosomes; mužské pohlaví; Cell Membrane; Cholesterol; Biological Transport; železité sloučeniny; Glutamic Acid; Rats, Wistar; Kinetics; silany; krysa rodu Rattus; potkani Wistar; kinetika; kyselina glutamová; Animals; beta-cyklodextriny; Ferric Compounds; Male; Silanes; presynaptická zakončení; cholesterol